Evaluasi Proses Kredensial Terhadap Kualitas Kerja Perawat Di Rumah Sakit Umum X Bandung - Umayah, Azzahra Khoirunnisa; Ariyani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
This research aims to evaluate the credential process on the quality of nurses' work at X Bandung General Hospital. The method used is quantitative with observation data collection techniques, and questionnaires. The population and sample used were 55 respondents, namely nursing employees at the X Bandung General Hospital. This study uses data analysis techniques: Validity Test, Reliability Test, and Spearman Rank Correlation Test. The results of the Spearman Rank Correlation Test show that changes in one variable do not have a significant effect on the other variables, however, there is still a positive relationship between the two variables can be seen from the correlation value of 0.168 and the significance of 0.221 meaning that when the value of "Cognitive Process" increases, then, The value of "quality of work" tends to increase as well. The obstacles found are a long enough time span for the collection of administrative files and limited resources at the time of credentialing.